Validating criteria for identifying core concepts using many-facet rasch measurement - McLaughlin, Jacqueline E.; Angelo, Thomas A.; White, Paul J. (Frontiers in Education, 2023)
Introduction Core concepts are foundational, discipline-based ideas considered necessary for students to learn, remember, understand, and apply. To evaluate the extent to which a concept is “core,” experts often rate concepts using various criteria, such as importance, complexity, and timeliness. However, there is a lack of validity evidence for core concepts criteria. Methods Using a three-facet Many-Facet Rasch Measurement (MFRM) model, we analyzed 7,558 ratings provided by 21 experts/raters for 74 pharmacology core concepts using five criteria measured on a five-point scale. Results All of the criteria had Infit or Outfit MnSq values within the expected range (0.5 < MnSq < 1.7), suggesting the criteria contained an acceptable amount of variability; a reliability index of approximately 1.00 suggested that the criteria were reliably separated with a high degree of confidence. The rating scale Outfit MnSq statistics also fell within the 0.5–1.7 model fit limits; the “average measure” and “Rasch-Andrich thresholds” increased in magnitude as the rating scale categories increased, suggesting that core concepts with higher ratings were in fact meeting the criteria more convincingly than those with lower ratings. Adjusting expert ratings using the MFRM facets (e.g., rater severity) resulted in reorganization of core concepts rankings. Conclusion This paper is a novel contribution to core concepts research and is intended to inform other disciplines seeking to develop, implement, and refine core concepts within the biomedical sciences and beyond.